N6-Methyladenosine in Cancer Immunotherapy: An Undervalued Therapeutic Target - Quan, Chao; Belaydi, Othmane; Hu, Jiao; Li, Huihuang; Yu, Anze; Liu, Peihua; Yi, Zhenglin; Qiu, Dongxu; Ren, Wenbiao; Ma, Hongzhi; Gong, Guanghui; Ou, Zhenyu; et al. (Frontiers in Immunology, 2021)
N6-methylation of adenosine (m6A), a post-transcriptional regulatory mechanism, is the most abundant nucleotide modification in almost all types of RNAs. The biological function of m6A in regulating the expression of oncogenes or tumor suppressor genes has been widely investigated in various cancers. However, recent studies have addressed a new role of m6A modification in the anti-tumor immune response. By modulating the fate of targeted RNA, m6A affects tumor-associated immune cell activation and infiltration in the tumor microenvironment (TME). In addition, m6A-targeting is found to affect the efficacy of classical immunotherapy, which makes m6A a potential target for immunotherapy. Although m6A modification together with its regulators may play the exact opposite role in different tumor types, targeting m6A regulators has been shown to have wide implications in several cancers. In this review, we discussed the link between m6A modification and tumor with an emphasis on the importance of m6A in anti-tumor immune response and immunotherapy.